IMPLEMENTATION OF ACADEMIC SUPERVISION IN IMPROVING TEACHERS' PEDAGOGICAL COMPETENCE - Tutik Yuliarsih; Maryanto; Ghufron Abdullah (Pena Cendekia Insani, 2025)
The purpose of this study is to describe and analyze the planning, implementation, and evaluation of academic supervision in improving the pedagogical competence of teachers at SDN Kalirejo 02 Ungaran Timur. This research is descriptive qualitative research, and the subjects of this study are school principals and teachers. The data collection techniques are interviews, documentation, and observation. The data analysis used is qualitative analysis, including data collection, data reduction, data display, and drawing conclusions. As for the data validity test, it uses source triangulation, technique triangulation, and time triangulation. The research findings indicate that: (1) The planning of academic supervision at SDN Kaliejo 02, East Ungaran, Semarang Regency, begins with several activities, including: developing a supervision program, setting goals and objectives, creating a schedule, and developing academic supervision instruments. (2) Academic supervision at SDN Kaliejo 02, Ungaran Timur, Semarang Regency, is conducted twice a year, namely at the beginning of the odd and even semesters. Academic supervision includes teacher administrative supervision and learning process supervision. Academic supervision is carried out based on the principles of objectivity, democracy, humanism, and sustainability. The techniques used are individual supervision techniques thru classroom visits, classroom observations, and individual meetings, and group supervision techniques thru meetings with teachers. (3) Evaluation of academic supervision is carried out by analyzing the results of teacher administrative supervision and learning process supervision. The follow-up actions include providing motivation, giving direct reprimands and guidance, and involving teachers in training/education activities, workshops, diklat, and KKG. Thru academic supervision, teachers' pedagogical competence improves, leading to better mastery of student characteristics, subject matter, curriculum development, the use of ICT in learning, the development of student potential, good communication with students, and the ability to conduct continuous assessment.